Allografts for Medial Patellofemoral Ligament (MPFL) Reconstruction in Adolescent Patients with Recurrent Patellofemoral Instability: A Systematic Review - Migliorini, Filippo; Maffulli, Nicola; Söllner, Stefan; Pasurka, Mario; Kubach, Joshua; Bell, Andreas; Betsch, Marcel (Children, 2023)
This systematic review updates the currently available evidence on medial patella-femoral ligament (MPFL) reconstruction using allografts. The outcomes were measured with patient-reported outcome measures (PROMs), redislocation and complication rates. This study was performed according to the 2020 PRISMA guidelines using the PubMed, Scopus, Web of Science databases, accessed in February 2023. Studies examining the clinical outcomes of MPFL reconstruction with allografts in adolescents and children with recurrent patellofemoral instability (PFI) were included. Data from three trials, including 113 surgical procedures in 121 children, were retrieved. 40% (48/121) of the included patients were girls. The mean age of the patients was 14.7 ± 0.8 years, and the mean follow-up length was 38.1 ± 16.5 months. With MPFL allograft reconstruction, the Kujala score improved by 14.7% (p < 0.0001) and the IKDC by 38.8% (p < 0.0001). The rate of dislocations was 5% (6 of 121), reoperation for instability was 11% (13 of 121), and subluxation was 2% (1 of 47). Conclusion: These results encourage the use of allografts for MPFL reconstruction in adolescent patients with recurrent patellofemoral instability. Though patellofemoral instability is common in clinical practice, the current literature lacks clinical evidence on allograft MPFL reconstruction. Additional high-quality investigations are required to properly establish the long-term advantages of allograft MPFL and its complication rate.
CRIS-Team Scopus Importer:2023-06-30
Keywords: adolescents; allograft; children; MPFL; patellofemoral instability